FBXO43 increases CCND1 stability to promote hepatocellular carcinoma cell proliferation and migration - Li, Chun-Ming; Zhang, Jie; Wu, Wu; Zhu, Zhu; Li, Feng; Wu, Di; Wang, Xiao-Jun; Xie, Chuan-Ming; Gong, Jian-Ping (Frontiers in Oncology, 2023)
Background and Aims: Abnormal expression of E3 ubiquitin ligase plays an important role in the development and progression of hepatocellular carcinoma (HCC), although the mechanism has remained elusive. This study aimed to investigate the biological function and potential mechanism of FBXO43 in HCC. Methods: FBXO43 expression in tissues and cells were detected by quantitative real-time PCR (qRT‒PCR), Western blot, and immunohistochemistry (IHC). The Kaplan-Meier method and Cox regression analysis were used to explore the correlation between the expression level of FBXO43 and the clinical survival. MTT assay, EdU incorporation, colony formation, Transwell, and wound healing assays were performed to evaluate the function of FBXO43 in cell proliferation and migration in vitro. The interaction between FBXO43 and cyclin D1 (CCND1) was assessed by co-immunoprecipitation (Co-IP) assay and in vivo ubiquitination assay. Results: We found that FBXO43 was upregulated in HCC patient tissues and positively associated with poor clinicopathological features. Meanwhile, HCC patients with high expression of FBXO43 had shorter overall survival (OS) and disease-free survival (DFS). Furthermore, knockdown of FBXO43 inhibited HCC cell proliferation, migration and epithelial-mesenchymal transition (EMT) in HCC cells. Mechanistically, FBXO43 interacted with CCND1 and promoted its stability by polyubiquitination, leading to HCC cell proliferation, migration and EMT. Functional rescue experiments demonstrated that knockdown of CCND1 blocks FBXO43-mediated cell proliferation and metastasis. Conclusions: FBXO43, as an independent prognostic biomarker, promotes HCC cell proliferation, metastasis and EMT by stability of CCND1, which provides a new potential strategy for HCC treatment by targeting FBXO43-CCND1 axis.